Constructing the trajectory of a small spacecraft for flying around the base spacecraft for the purpose of external inspection and estimating the energy costs for the flyby maneuver - V. I. Ruban; V. N. Blinov; V. V. Kositsyn; A. I. Lukyanchik; P. S. Yachmenev; P. V. Stepen (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2023)
The paper presents a methodology for constructing a flyby trajectory of a base spacecraft for the purpose of inspecting it using a small spacecraft carried on board and estimating the required characteristic velocity reserves for the flyby maneuver. The use of approximate calculation methods made it possible to obtain the simplest dependences of trajectory parameters with high accuracy. The technique allows not only to estimate the energy costs for orbital maneuvers, but also allows one to calculate the values of control impulses for the real problem of controlling the motion of a small spacecraft relative to the base spacecraft.